High-Performance Liquid Chromatographic Ultraviolet Determination of Memantine Hydrochloride after In Vitro Transdermal Diffusion Studies - Sergio del Rio-Sancho; César E. Serna-Jiménez; M. Aracely Calatayud-Pascual; Cristina Balaguer-Fernández; Andrés Femenía-Font; Virginia Merino; Alicia López-Castellano (Journal of Chemistry)
The purpose of the present work was to validate an accurate and precise high-performance liquid chromatography (HPLC) method involving ultraviolet detection for the quantitative analysis of memantine hydrochloride. In order to analyze a molecule with no chromophoric groups that could be detected by a UV/visible detector, it was necessary to extract the drug and to perform a dansylation reaction that enabled the UV/visible detection of the derivatized molecule. Separation was carried out with a 150 mm Kromasil C18 column at room temperature. The detection response, at 218 nm, was found to be linear in the concentration range from 0.5 to 50 μg/mL. The method was validated for specificity, linearity, precision, accuracy, limit of detection, limit of quantification, and robustness. The limit of detection (LOD) was 0.144 μg/mL, and the limit of quantification (LOQ) was 0.437 μg/mL. The dansylated memantine complex was stable for at least five days in all the conditions evaluated. The potential use of this method has been demonstrated by the quantification of memantine hydrochloride contained in samples from the study of its in vitro transdermal permeation.